The impact of a training approach to develop the speed and level of technical performance of a straight punch according to the different punching distances of young boxers - Thaer Khamis Ahmed, (Eximia, 2023)
The goal of the research to prepare a training approach to develop the speed and level of technical performance of the straight punch according to the different punching distances according to the different punching distances for young boxers, as well as to identify the impact of the training method in the development of the speed and level of technical performance of straight punches according to the different punching distances of young boxers, and is considered to be the payment of various punches and influential from different punching distances on the competitor and under the changing and rapid punching conditions of the most important factors of the success of the implementation of offensive and defensive duties during the game, where the researcher used the experimental method to solve the problem of research, and was chosen the researcher used the experimental method to solve the problem of research, and was chosen the choice of the researcher The design of the two equal groups with pre and post-tests randomly selected, as the research sample consisted of young boxing players in sports clubs in Diyala province, namely (Baquba, Zuhairat) ages (17-18) years for the category : The training curriculum prepared by the researcher helped greatly in developing the speed and level of technical performance of the straight punch according to the different punching distances of the research sample members . The research sample enjoyed a high level in the execution of the straight punch according to the different punching distances, as the average punching distance was characterized by preference followed by the long punching distance and then the short distance . The experimental group enjoyed an advantage compared to the control group in developing the speed and level of technical performance of the straight punch according to the different punching distances of the research sample members. The researcher reached several recommendations Using the training method prepared by the researcher in training boxing teams for young people to achieve a high technical level and better athletic achievements . Increase the concentration and attention of the trainers in the training of punches according to different punching distances in parallel. Conduct similar research on different samples and other functional variables.